Decreasing Sedentary Behavior: Effects on Academic Performance, Meta-Cognition, and Sleep - Pilcher, June J.; Morris, Drew M.; Bryant, Stewart A.; Merritt, Paul A.; Feigl, Hayley B. (Frontiers in Neuroscience, 2017)
There is growing interest in using activity workstations as a method of increasing light physical activity in normally sedentary environments. The current study (N=117) compared the effects of studying in college students while slowly pedaling a stationary bike with a desktop with studying at traditional desks across 10 weeks in an academic semester. The students were assigned to study either on the stationary bike or at a traditional desk located in the campus library for a minimum of 2 hours a week. During the 10 weeks, the students studied for tests or worked on other required academic activities while working at their assigned desk. In addition, the participants completed a pre survey, weekly surveys, and a post survey. We found that although students studying at the traditional desks reported more ease of studying and more effective studying than those using the stationary bikes, the two groups performed equally well on tests in an introductory psychology course. Moreover, the students using the traditional desks reported a decrease in sleep quality later in the semester while those using the activity workstation reported stable levels of sleep quality. The current results indicate that activity workstations could be implemented in university settings to encourage light physical activity without negatively affecting academic performance while providing possible long-term health and well-being benefits. Furthermore, the results suggests that activity workstations could be a means of combating sedentary behavior in environments where individuals are expected to sit either while waiting (e.g., doctor’s waiting rooms, airports) or when completing a necessary task (e.g., the workplace, educational settings).